(untitled) (Bangladesh Journal of Medical Science, 2018)
AMP-activated protein kinase (AMPK) and c-AMP-response element binding protein (CREB) are found to be important proteins in metabolic system. AMPK has become the focus as a novel therapeutic target for the treatment of metabolic syndromes. Oyster mushroom is traditionally used as remedy of diabetes and hypertension. The present study aims to observe the stimulation of AMPK and CREB in streptozotocin-induced diabetic model rats through Oyster mushroom administration. Long Evan’s rats were used to create type 2 model diabetic rats through intraperitoneal injection of streptozotocin at 90mg/kg body weight of 48hr old pups. Rats were divided into three groups: diabetic control rats, glibenclamide treated diabetic rats (positive control) and mushroom treated diabetic rats (experimental group). Mushroom was administered orally at a dose of 1.25g/kg body weight in semisolid forms. After five weeks rats were sacrificed, serum and tissues were collected for future analysis. Glucose was measured using glucose-oxidase method, lipid profile by enzymaticcolorimetric method. Proteins from different tissues were extracted using RIPA cell lysis buffer, AMPK and CREB were identified using western blot and immuno-precipitation techniques. A significant decreased of fasting glucose was found after 35 days of experiment when it compared with control diabetic rats (M ± SD, mmol/l, Diabetic control group: 8.0±1.1; Mushroom treated diabetic group: 6.4±1.0; p=0.021). Glibenclamide treated diabetic rats have also shown decreased fasting glucose compared to control diabetic rats. In paired ‘t’ test analysis, it has been found that serum fasting glucose level was significantly decreased on 35th day compared the 0 day in both mushroom treated group (p=0.027) and in glibenclamide treated group (p=0.005). Serum TG level was decreased on 35th day compared to 0day in mushroom treated diabetic model rats only (M±SD, mg/dl, 0 day: 84±13; 35th day: 61±6, p=0.002). No significant changes of cholesterol, HDL and LDL were noticed in the experimental groups following treatment with mushroom. Western blot analyses have shown increased band intensity of AMPK and p-CREB in mushroom treated diabetic model rats. Therefore, it can be concluded that Anti-hyperglycemic property of Oyster mushroom could be explained through increased expression of AMPK and activation of CREB. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.661-668